Microbiota as a new pathogenetic factor in the development of chronic hyperuricemia and gout. Part 2: gout therapy and the gut microbiota - M. S. Eliseev; E. N. Kharlamova; O. V. Zhelyabina; A. M. Lila (Современная ревматология, 2022)
The article presents current data on the effect of drugs for the treatment of gout on the composition and function of the intestinal microbiota. The potential possibilities of pre- and probiotics use for the prevention and complex therapy of gout are discussed, therapeutic effect may be associated with their impact on the uric acid synthesis and intestinal excretion, as well as with anti-inflammatory properties. The need for further research in this area is emphasized.